Pemetaan Prioritas Pengembangan Kereta Api Barang Berbasis Sebaran Volume Angkutan di Indonesia - Jumali, Muhamad Abdul; Nata, Aan Hadi; Pamungkas, Muhammad Aji (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study maps development priorities for rail freight in Indonesia based on the spatial distribution of freight volume by major island groups. A descriptive quantitative approach was applied using secondary data on rail freight volume (thousand tons) across five island groups. The analysis includes volume tabulation, share calculations, Java-to-other regions dominance ratios, and a Java versus non-Java aggregate comparison. Results indicate a total of 33.0 million tons, dominated by Java at 18.5 million tons (56.06%), followed by Sumatra 7.2 (21.82%), Kalimantan 4.1 (12.42%), Sulawesi 2.3 (6.97%), and Bali–Nusa Tenggara 0.9 (2.73%). The dominance ratio of Java reaches 20.56 over Bali–Nusa Tenggara and 8.04 over Sulawesi, while non-Java accounts for 43.94% (14.5 million tons). These findings support prioritizing rail freight development outside Java through strengthened logistics nodes and intermodal integration.